2020
DOI: 10.2147/jmdh.s246253
|View full text |Cite
|
Sign up to set email alerts
|

<p>Frequency of Use, Perceptions and Barriers of Information and Communication Technologies Among Latin American Physicians: An Ecuadorian Cross-Sectional Study</p>

Abstract: In recent years, the use of information and communication technologies (ICTs) has increased in various sectors, among which the healthcare service is no exception. However, studies have mostly focused on the use of ICTs among patients with chronic diseases, with few reports on the advantages and barriers of these technologies among physicians, particularly in Latin America. We designed this study to fill in the gap, as an objective assessment of the frequency of use, perceptions, and barriers of ICTs among phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 41 publications
1
40
1
2
Order By: Relevance
“…In conclusion, our study found a high use of ICTs among Ecuadorian dentists, a finding that compares to previous reports among physicians and nurses in the country [13,31]. But despite the potential benefits of these technologies, there are many barriers and factors that need to be accounted when implementing ICTs.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In conclusion, our study found a high use of ICTs among Ecuadorian dentists, a finding that compares to previous reports among physicians and nurses in the country [13,31]. But despite the potential benefits of these technologies, there are many barriers and factors that need to be accounted when implementing ICTs.…”
Section: Discussioncontrasting
confidence: 47%
“…An anonymous, cross-sectional survey-based study was completed by 342 Ecuadorian dentists. We adapted the questionnaire from a previous survey used in physicians [13]. The questionnaire surveyed demographic characteristics and recorded the frequency of use, perceptions and barriers of ICTs using a 5-point Likert scale.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…In conclusion, our study found a high use of ICTs among Ecuadorian dentists, a finding that compares to previous reports among physicians and nurses in the country [13,31]. But despite the potential benefits of these technologies, there are many barriers and factors that need to be accounted when implementing ICTs.…”
Section: Discussionsupporting
confidence: 44%
“…An anonymous, cross-sectional survey-based study was completed by 342 Ecuadorian dentists. We adapted the questionnaire from a previous survey used in physicians (8). The questionnaire surveyed demographic characteristics and recorded the frequency of use, perceptions and barriers of ICTs using a 5-point Likert scale.…”
Section: Materials and Methods Study Design And Populationmentioning
confidence: 99%